Analytical investigation of thermoelectric performance for cooling application - Kin, L.K. (Penerbit Akademia Baru, 2018)
This paper presents the method used to predict the internal parameters of thermoelectric module (TEM) and the several factors that affect the temperature reduction of air in Thermoelectric (TE) cooling system. A TE cooling system consists of three TEMs attached on the top of an air duct with the dimensions 9.3 cm Ã 9.3 cm Ã 55 cm. Ambient air flows through the duct and its outlet temperature is estimated by using the log mean temperature difference (LMTD) method for different weather conditions. At the considered conditions, results showed that 6 A is the optimum operating current, and the maximum temperature reduction can reach to 2.41 Â°C. The performance of TE cooling system strongly depends on the ambient condition and for the considered 40 hours weather conditions, the maximum temperature reduction happened at around 3 pm. It was also found that the increase of inlet air velocity causes the temperature reduction to decrease exponentially. As a result, this study identified the correlate effects of the ambient weather, the operating current and the air velocity on the TE cooling system. As one does not have control on the ambient weather, selecting the optimum operating current level and inlet air velocity of the system is important to fully utilize the cooling effect of the system. Â© 2016 Penerbit Akademia Baru.